1982
DOI: 10.1093/ajcn/35.3.609
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric assessment of nutritional status in pregnant women: a reference table of weight-for-height by week of pregnancy

Abstract: A reference table of weight-for-height by week of pregnancy has been devised on theoretical grounds, based on the premises that the average increment of weight during pregnancy is 20% of the prepregnant weight and that almost all the increment takes place linearly during the 2nd and 3rd trimesters of pregnancy. The table was tested with retrospective clinic and hospital data. The results show a good correlation between the weight-for-height at different stages of pregnancy as a percentage of the reference tabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
4

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 15 publications
0
26
0
4
Order By: Relevance
“…Likewise, periodontal disease with poor oral hygiene has been linked with preterm labor (37), but the Tanzanian women studied here did not present with acute periodontal disease as identified during The percent deviation was calculated based on the participant's gestational age (calculated from participant recall of the last menstrual period) and height as measured at baseline. These were used to determine the ideal weight of the participants as outlined by Gueri et al (25). The weight of the participants measured at baseline was then used to calculate the percent deviation from the ideal weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, periodontal disease with poor oral hygiene has been linked with preterm labor (37), but the Tanzanian women studied here did not present with acute periodontal disease as identified during The percent deviation was calculated based on the participant's gestational age (calculated from participant recall of the last menstrual period) and height as measured at baseline. These were used to determine the ideal weight of the participants as outlined by Gueri et al (25). The weight of the participants measured at baseline was then used to calculate the percent deviation from the ideal weight.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm, or if last menstrual period was unavailable, approximation of gestational age was based upon measurement of fundal height. Originally, participants were further grouped into states of nutritional status (nourished or undernourished) based upon having a mid-upper-arm circumference (MUAC) of Ͻ235 mm if undernourished, and deviations from expected weight for gestational age (25). Since this was a pilot study, sample size was based on participant availability.…”
Section: Methodsmentioning
confidence: 99%
“…The retrospective nature of the study did not allow us to obtain prepregnancy weights, so mother's weight at 8±10 weeks postconception was used as a proxy for her prepregnancy weight. Gueri et al (1982), have suggested that there is an increase of only 1.7% over the prepregnant weight during the ®rst 13 weeks of pregnancy. In this group of mothers, 13% had a BMI 19, suggesting that they entered pregnancy on a lower nutritional plane, and we have shown previously that mothers with thinner triceps skinfolds had children who at age 11 y had higher blood pressures (Godfrey et al, 1994).…”
Section: Maternal Nutritional Status M Thame Et Almentioning
confidence: 99%
“…Desde la década de los 40, se han elaborado múltiples gráficas para evaluar el estado nutricional de la embarazada en el continente americano. Las más conocidas en Estados Unidos son la de Chesley, 1944; la de Tompkins y Wiehl, 1951; la de Hytten y Leitch, 1971 (19); la de Gueri y col., 1982 (19,20); la de Rosso P., 1985 (19,21); la de Brown y col., 1986 (19); la de Husaini, 1986 (19); la de Dimperio, 1988 (19), y la del Instituto de Medicina de Estados Unidos, 1990 (2,22,23).…”
unclassified